Legal Protection for Foreign Investors in Infrastructure Projects Supporting Mining Downstreaming in Indonesia: A Systematic Literature Review - Sandi Saputra; Sami'an Sami'an; Sarwono Hardjomuljadi; Dwi Edi Wibowo (International Journal Labs, 2026)
The article aims to identify legal issues and legal solutions that affect legal protection for foreign investment in infrastructure and downstream projects in Indonesia. The analysis uses a systematic literature review method. The focus of the analysis lies in four areas: (1) enforcement of arbitral awards (New York Convention 1958; Law 30/1999), (2) the position of arbitration (seat), lex arbitri, and the standard of